2009
DOI: 10.1111/j.1532-5415.2009.02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐one‐item Fall Risk Index Predicts Falls in Elderly Community‐dwelling Japanese

Abstract: Labor has developed a 21-item Fall Risk Index (FRI) 2 for early detection of the risk of falls in elderly people. It has been found that fallers are older, more disabled, and more depressed and had higher scores on the FRI than nonfallers 3 and that FRI score was closely associated with aging and sex differences in community-dwelling elderly persons in Japan. 4 Although the significance of the FRI has been demonstrated in cross-sectional settings, the cutoff score for predicting falls in elderly people has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…We measured dorsiflexion and Fall Risk Index (FRI), 1,2 including the history of falls within the past year, in 131 women (46–89 years, mean age 78.0 ± 7.1 years) and 88 men (46–93 years, mean age 76.2 ± 8.6 years) who visited the fall prevention clinic in Kyorin University Hospital. The occurrence of falls within the past year was 35.6%.…”
contrasting
confidence: 94%
“…We measured dorsiflexion and Fall Risk Index (FRI), 1,2 including the history of falls within the past year, in 131 women (46–89 years, mean age 78.0 ± 7.1 years) and 88 men (46–93 years, mean age 76.2 ± 8.6 years) who visited the fall prevention clinic in Kyorin University Hospital. The occurrence of falls within the past year was 35.6%.…”
contrasting
confidence: 94%
“…In our previous cross‐sectional study, we found that fallers were older, more disabled, more depressed and had higher FRI‐21 scores than non‐fallers 3 . We also showed that FRI‐21 score was closely associated with age and sex differences, 9 and that a cut‐off of 9/10 was a useful predictor of falls in Japanese community‐dwelling elderly 10 . History of falls is a known fall risk, 11 and falls themselves are closely correlated with dependence of BADL.…”
Section: Introductionmentioning
confidence: 59%
“…Each item received a score of 1 (risk present) or 0 (risk absent), and the sum of all items ranged from 0 (low fall risk) to 21 (high fall risk), with higher scores indicating higher risk of falls. A cut‐off point of 9/10 on the 21‐item FRI‐21 is useful for early detection of fall risk 10 …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that cognitive impairment can reduce an individual's independence while performing basic and instrumental activities of daily living; moreover, cognitive ability is one major factor for predicting falls in elderly individuals (Wada et al, 2009). However, cognitive impairment is rarely assessed in clinical and research trials on stroke patients; physical and functional impairments are generally assessed.…”
Section: Discussionmentioning
confidence: 99%